Myofibroblast transdifferentiation is associated with changes in cellular and extracellular vesicle miRNA abundance. - Siti Amalina Inche Zainal Abidin (Public Library of Science (PLoS), 2021)
Transforming growth factor-beta 1 (TGF-β1), a pro-fibrotic tumour-derived factor promotes fibroblast differentiation in the tumour microenvironment and is thought to contribute to the development of pro-tumourigenic cancer-associated fibroblasts (CAFs) by promoting myofibroblast differentiation. miRNA dysregulation has been demonstrated in myofibroblast transdifferentiation and CAF activation, however, their expression varies among cell types and with the method of fibroblast induction. Here, the expression profile of miRNA in human primary oral fibroblasts treated with TGF-β1, to derive a myofibroblastic, CAF-like phenotype, was determined compared to untreated fibroblasts. Myofibroblast transdifferentiation was determined by the expression of alpha-smooth muscle actin (α-SMA) and fibronectin-1 extra domain A (FN-EDA1) using quantitative real-time PCR (qRT-PCR) and western blot. The formation of stress fibres was assessed by fluorescence microscopy, and associated changes in contractility were assessed using collagen contraction assays. Extracellular vesicles (EVs) were purified by using size exclusion chromatography and ultracentrifugation and their size and concentration were determined by nanoparticle tracking analysis. miRNA expression profiling in oral fibroblasts treated with TGF-β1 and their extracellular vesicles was carried out using tiling low-density array cards. The Database for Annotation, Visualization, and Integrated Discovery (DAVID) was used to perform functional and pathway enrichment analysis of target genes. In this study, TGF-β1 induced a myofibroblastic phenotype in normal oral fibroblasts as assessed by expression of molecular markers, the formation of stress fibres and increased contractility. TaqMan Low-Density Array (TLDA) analysis demonstrated that miR-503 and miR-708 were significantly upregulated, while miR-1276 was significantly downregulated in TGF-β1-treated oral fibroblasts (henceforth termed experimentally-derived CAF, eCAF). The gene functional enrichment analysis showed that the candidate miRNAs have the potential to modulate various pathways; including the Ras associated protein 1 (Rap1), PI3K-Akt, and tumour necrosis factor (TNF) signalling pathways. In addition, altered levels of several miRNAs were detected in eCAF EV, including miR-142 and miR-222. No differences in size or abundance of EV were detected between eCAF and normal oral fibroblast (NOF). Little overlap was observed between changes in cellular and EV miRNA profiles, suggesting the possibility of selective loading of EV miRNA. The study reveals miRNA expression signature could be involved in myofibroblast transdifferentiation and the miRNA cargo of their EV, providing novel insight into the involvement of miRNA in CAF development and function.